The Relationship between Knowledge, Social Media and Religioosity and Premarital Sexual Behavior in Adolescents at SMK 1 Yapenda, Kedungwuni, Pekalongan - Kustri Viana; Nugroho, Santoso; Dani Prastiwi (PENA NURSING, 2025)
ABSTRAC Background: Adolescence begins with puberty, which is a time when physical and physiological changes occur, resulting in perceptions and attraction to the opposite sex, which can give rise to sexual urges. Sexual behavior is any behavior that is driven by sexual desire, whether with the opposite sex or the same sex. Pre marriage sexual behavior among teenagers in Indonesia is very concerning and can have negative impacts such as pregnancy, abortion and IMS. Several influencing factors is knowledge, social media and religiosity. Objective: To determine the correlation between knowledge, social media, religiosity and pre marriage sexual behavior in adolescents at SMK Yapenda 1 Kedungwuni, Pekalongan Regency. Methods: The quantitative descriptive correlational research method with a cross-sectional approach. Using a questionnaire instrument. The sample used was 82 students in grades X and XI. Data was analyzed using the Spearman Rank test. Results: The results of the Spearman Rank test showed that there was a correlation between knowledge and premarital sexual behavior in adolescents with a p-value of 0.041 <0.05. There was a correlation between social media and pre mariage sexual behavior in adolescents with a p-value of 0.013 < 0.05. There was no correlation between religiosity and pre marriage sexual behavior in adolescents with a p-value of 0.238 > 0.005. Conclusion: There is a correlation between knowledge and social media towards pre marriage sexual behavior in adolescents. There is no correlation between religiosity towards pre marriage sexual behavior in adolescents.